Atomistic modeling of parylene-metal interactions for surface micro-structuring - Vasenkov, Alex V. (Journal of molecular modeling, 2011)
Many applications, ranging from neural prosthetics and cardiac rhythm management systems to organics-based flexible display, can benefit from the engineering of parylene-metal-parylene structures via selective deposition. Despite several experimental studies, the mechanism responsible for this selective deposition is not clear and is the subject of the current paper. Towards this goal, we used the quantum semiempirical Hamiltonian (QSH) solver coupled to a molecular dynamic (MD) model, which is particularly suited to study parylene-metal interactions due to its ability to determine the different pathways of the transformations involving making and breaking of chemical and physical bonds. The simulation results of selective deposition of various parylene chains on titanium dioxide and gold surfaces are presented. Time-dependent bond orders were used to quantify the deposition process. The mechanism of metal atom adhesion to parylene was also discussed to provide insights into the formation of defects in metal/parylene interfaces.